Perkiraan Kadar Seftazidim dalam Darah pada Pasien Pneumonia dengan Gangguan Fungsi Ginjal - Dewi Latifatul Ilma; Djoko Wahyono; Ika Puspita Sari (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Pneumonia is one of the major causes of mortality due to infection in hospitalized patients. It was frequently found in patients with renal failure. Clinical outcomes of infected patients with renal failure are worse compared to patients without renal failure. The presence of renal impairment affects the pharmacokinetics of the drug. Ceftazidime is one of the most commonly used antibiotics in patients with pneumonia. Approximately, 80-90% of ceftazidime’s total drug fraction is eliminated by kidneys so that the presence of kidney disorders will affect the concentration of ceftazidime in the blood. This study aimed to determine the estimated concentration of ceftazidime in the blood and clinical outcome of pneumonia patients with renal impairment. This study was a retrospective study with descriptive observational design. Data were obtained from patient’s medical record in a hospital in Yogyakarta between January 2013-June 2017 which fulfilled the inclusion criteria, i.e., ≥18 years old patients with complete medical record data, treated in internal medicine ward with diagnosis of pneumonia (HAP/HCAP) who had chronic renal failure, and received ceftazidime for minimum 72 hours or 3 days. The number of research samples were 40 patients. This study showed that 31 patients (77.5%) had achieved estimated ceftazidime concentration in the blood above the minimum inhibitory concentration of 8 μg/ mL. After ceftazidime therapy, 19 patients (47.5%) had improved clinical outcome and 21 patients (52.5%) had not improved clinical outcome.